Does iron reduction control the release of dissolved organic carbon and phosphate at catchment scales? Need for a joint research effort. (15th July 2017) - Musolff, Andreas; Selle, Benny; Büttner, Olaf; Opitz, Michael; Knorr, Klaus‐Holger; Fleckenstein, Jan H.; Reemtsma, Thorsten; Tittel, Jörg
Abstract : Increasing concentrations of dissolved iron and DOC are likely linked to decreasing nitrogen depositon.